Body dysmorphic concerns, social adaptation, and motivation for psychotherapeutic support in dermatological outpatients. (September 2016) - Ritter, Viktoria; Fluhr, Joachim W.; Schliemann‐Willers, Sibylle; Elsner, Peter; Strauß, Bernhard; Stangier, Ulrich
Summary: Background and objectives: Dermatologists are increasingly confronted with patients affected by body dysmorphic disorder (BDD). BDD is characterized by excessive preoccupation with one or more perceived defect(s) or flaw(s) in physical appearance which are not observable or appear slight to others. So far, there have been only few studies examining the prevalence of BDD in dermatological outpatients. In addition, the need for psychotherapeutic support in dermatological outpatients with body dysmorphic concerns has not yet been systematically examined. The objective of the present study was therefore to investigate the frequency of body dysmorphic concerns as well as social adaptation and the need for psychotherapeutic support in the aforementioned patient group. Patients and methods: A total of 252 dermatological outpatients seen at a German university hospital were consecutively enrolled, and examined using the Dysmorphic Concerns Questionnaire, the Social Adaptation Self‐Evaluation Scale, and the German version of the University of Rhode Island Change Assessment Scale. Results: 7.9 % of all outpatients (unselected sample) showed positive test results, suggesting clinically relevant body dysmorphic concerns. Patients with clinically relevant body dysmorphic concerns exhibited poor social adaptation. Contrary to expectations, these patients revealed a high motivation for change, indicating the necessity for psychotherapeutic support. Conclusions: Our findings confirm previous prevalence rates of BDD in dermatological outpatients, and highlight the need for providing psychotherapeutic support to dermatological patients.